A Review of Randomized Controlled Trials Utilizing Telemedicine for Improving Heart Failure Readmission: Can a Realist Approach Bridge the Translational Divide?. Issue 13 (July 2019) - Gonzalez Garcia, Manuel; Fatehi, Farhad; Bashi, Nazli; Varnfield, Marlien; Iyngkaran, Pupalan; Driscoll, Andrea; Neil, Christopher; Hare, David L; Oldenburg, Brian
Background: Telemedicine and digital health technologies hold great promise for improving clinical care of heart failure. However, inconsistent and contradictory findings from randomized controlled trials have so far discouraged widespread adoption of digital health in routine clinical practice. We undertook this review study to summarize the study outcomes of the use of exploring the evidence for telemedicine in the clinical care of patients with heart failure and readmissions. Methods: We inspected the references of guidelines and searched PubMed for randomized controlled trials published over the past 10 years on the use of telemedicine for reducing readmission in heart failure. We utilized a modified realist review approach to identify the underlying contextual mechanisms for the intervention(s) in each randomized controlled trial, evaluating outcomes of the intervention and understanding how and under what conditions they worked. To provide uniformity, all extracted data were synthesized using adapted domains from the taxonomy for disease management created by the Disease Management Taxonomy Writing Group. Results: A total of 12 papers were eligible, 6 of them supporting and 6 others undermining the use of telemedicine for improving heart failure readmission. In general terms, those studies not supporting the use of telemedicine were multicentre, publicly funded, with large amount of participants, and long duration. The patients had also better rates of treatment with angiotensin-converting enzyme inhibitors/angiotensin II receptor blocker and beta-blockers, and telemonitoring and automatic transmission of vital signs were less utilized, in comparison with the studies in which telemedicine use was supported. The analysis of the environment, intensity, content of interventions, method of communication, quality of the underlying model of care and the ability, capability, and interest from health workers can help us to envisage probabilities of success of telemedicine use. Conclusions: A realist lens may aid to understand whom and in which circumstances the use of telemedicine can add any substantial value to traditional models of care. Wider outcome criteria beyond major adverse cardiovascular events, for example, cost efficacy, should also be considered as appropriate for effecting guidelines on care delivery when robust prognostic therapeutics already exist.